Visual subtexts and sexuality narratives in the Kenyan Disconnect 2 and Nafsi Films - Oiye, Fredrick Ogutu; Mwangi, Michael Kamau; Mokua, Elias; Muchemi, Leah Wangui (Nairobi Journal of Humanities and Social Sciences, 2024)
This paper explores the relationship between visual subtexts and sexuality narratives in Kenyan films. Visual texts play a crucial role in the hierarchy of film messaging, and understanding how these subtexts frame sensitive topics such as sexuality is essential. Through key informant interviews and examination of specific scenes and subtext elements like décor, space, and costumes, the study concludes that the three subtexts were significantly utilized to complement the explicit sexual narratives, particularly in socially and ethically sensitive portrayals of sexuality acts and moments. The study recommends a more strategic approach to the utilization of the cinematic and mise-en-scene visual subtexts in communicating sexuality in films.